Pengembangan Aplikasi Android Rekomendasi Tempat Wisata di Malang Raya dengan Group Decision Support System dan Location-Based Service - David Hosea Sipahutar; Ratih Kartika Dewi; Muhammad Aminul Akbar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Malang Raya is known as a choice of famous tourist destinations in Indonesia. This can be seen from the increase in tourists visiting this area from 2016 to 2018. This increase originated from the growth of tourist attractions with the theme of natural tourism, heritage, and also food. Therefore, a system is needed, in this case, an application, as a tourist reference in Malang Raya. In 2019, two similar studies were carried out by Jodie Rizky Hidayat in Batu City and Ricky Irfandy in the Malang area. Their approach to recommendations is through individual input. In this study, the application focuses on a group recommendation approach. Therefore, this study uses the Group Decision Support System theory. The value of the recommendation obtained from the use of the TOPSIS-Borda theory. After implementing the application, the application is tested with three tests. The test is carried out by using the white-box and black-box methods, testing the algorithm manual, and testing it in terms of usability. From these tests, it was found that the application runs according to specifications with a valid value of 100%, and the algorithm runs according to manual calculations. From usability testing, it is known that the application can be accepted by users with a score of 72.5.